Comparison effectiveness of e-booklets and videos based on SESD on students' analytical thinking skills - Utomo, Pambayun Wahyu; Muna, Izza Aliyatul (JPBIO (Jurnal Pendidikan Biologi), 2024)
Analytical thinking skills are essential in science learning because they involve investigating a concept in everyday life, which is a product, fact, principle, and theory, and applying scientific methods as a problem-solving process. However, the analytical thinking skills possessed by junior high school students still need to improve. So, using media is one solution to improving analytical thinking skills. This research compares the effectiveness of SESD-based e-booklet media and SESD-based videos on analytical thinking skills. The method used includes quantitative comparative, which compares the effect of using e-booklets and SESD-based videos and tests the effectiveness of both media. The data analysis used was the Wilcoxon Test and effect size Cohen’s d. The results of this study explain that video media and e-booklets influence analytical thinking skills. Still, SESD-based video media is superior to SESD-based e-booklet media in improving students' analytical thinking skills. The e-booklet and video media based on Science Education for Sustainable Development (SESD) is a learning media that integrates sustainable development education (ESD) into science learning, which contains the values of sustainable development for the future. So, the conclusion is that SESD-based video media is more effective than SESD-based e-booklet media.